Lima in the Peruvian Traditions of Ricardo Palma - Martos Carrera, Marco (2020)
The Peruvian Traditions of Ricardo Palma, read and enjoyed by many generations, have been studied by critics from different perspectives, and from most people who know them they express in a peculiar way the events of life in Peru during the 16th, 17th, 18th and 19th centuries through the most varied characters from different social strata. The importance of Lima has been noticed in the center of this narrative work. The text intends to specify the preponderant place of the City of Kings in the most important narrative work of our writer. And to analyze some forms of composition in this multiple book.